Climate and grazing control nurse effects in an Ecuadorian dry shrubby community - Espinosa íñiguez, C. (2017)
Abstract: Positive plant interactions have strong effects on plant diversity at several spatial scales, expanding species distribution under stressful conditions. We evaluated the joint effect of climate and grazing on the nurse effect of Croton wagneri, by monitoring several community attributes at two spatial scales: microhabitat and plant community. Two very close locations that only differed in grazing intensity were surveyed in an Ecuadorian dry scrub ecosystem. At each location, two 30 30-m plots were established at four altitudinal levels (1500, 2630, 1959 and 2100 m asl) and 40 microsites were surveyed in each plot. Croton wagneri acted as community hubs, increasing species richness and plant cover at both scales. Beneath nurses mean richness and cover values were 3.4 and 21.9%, and in open areas 2.3 and 4.5%, respectively. Magnitude of nurse effect was dependent on climate and grazing conditions. In ungrazed locations, cover increased and diversity reduced with altitude, while grazed locations showed the opposite trend. In ungrazed plots the interactions shifted from positive to negative with altitude, in grazed locations interactions remained positive. We conclude that the nurse effect is a key mechanism regulating community properties not only at microsite but also at the entire community scale. Copyright © Cambridge University Press 2013.